1978
DOI: 10.1139/z78-155
|View full text |Cite
|
Sign up to set email alerts
|

A cytological description of sibling species of Simulium venustum and S. verecundum with standard maps for the subgenus Simulium Davies (Diptera)

Abstract: The paper proposes standard polytene chromosome maps for species groups in the subgenus Simulium. In the S. venustum/verecundum complex we distinguish by their chromosomes a minimum of seven sibling species designated by their IIS sequences, as follows: EFG/C (S. truncatum?) holarctic; EFG, Germany; CC (S. venustum?) North America (with probably CC 1 a separate sibling); A/C venustum, New Hampshire (with AC(gB) venustum Newfoundland probably distinct); CC 2 Ontario, Newfoundland; AA verecundum Newfoundland (wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
149
2

Year Published

1979
1979
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(155 citation statements)
references
References 7 publications
4
149
2
Order By: Relevance
“…Chromosome terminology, including names of markers, follows that of Rothfels et al [1978] and Adler et al [2004]. Numbering of chromosome sections follows the standard map of the subgenus Simulium for IS, IL, IIL, and IIIS [Rothfels et al, 1978] and IIS and IIIL [Tangkawanit et al, 2009].…”
Section: Cytological Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Chromosome terminology, including names of markers, follows that of Rothfels et al [1978] and Adler et al [2004]. Numbering of chromosome sections follows the standard map of the subgenus Simulium for IS, IL, IIL, and IIIS [Rothfels et al, 1978] and IIS and IIIL [Tangkawanit et al, 2009].…”
Section: Cytological Studymentioning
confidence: 99%
“…subgenus Simulium was proposed by Rothfels et al [1978] to compare species related to the subgenus. However, after examination of more species, it was found that the short arm of chromosome II (IIS) and the long arm of chromosome III (IIIL) were limited to the North American Simulium venustum group.…”
mentioning
confidence: 99%
“…To make species identifications, chromosome-banding patterns were compared with standard maps available in the literature (e.g. Rothfels et al, 1978) or on file in the laboratory of Adler. For both the spring and summer collections, two species pairs (Simulium fibrinflatum/notiale, Simulium venustum/verecundum) were taxonomically unresolved at the time of this study and were thus excluded from consideration when their identities could not be confirmed.…”
Section: Study Area and Sampling Regimementioning
confidence: 99%
“…Chromosomal landmarks are consistently found within an arm and, therefore, aid arm recognition (Rothfels et al, 1978). A primary nucleolar organizer can appear anywhere in the complement, though its location is consistent at some taxonomic level (Adler et al, 2004).…”
Section: Introductionmentioning
confidence: 99%